Is crop insurance creating welfare gain in North-East China: how to improve policy implementation? - Le, Shengyue, Sanglestsawani, Bunyasiri and Suchato, Ravissa
The article evaluates the expected welfare gain from voluntary partial government-subsidized maize insurance in north-east China. A total of 356 maize-growing households$1 (Brisk preferences from Linkou County of Heilongjiang province are examined and their expected welfare gains were analysed by the expected utility theory with each farmer$1 (Bs unique risk preference. The research found that 217 out of 356 households are rational decision-makers and most of them are risk averse. In term of expected welfare gain, the research pointed out that providing the existing crop insurance creates a welfare gain of about CNY 177 per hectare. However, this estimated welfare gain might be reduced to only CNY 124 per hectare if the local government decided to provide 100 per cent insurance premium subsidy with a lower level of protection at the same fiscal budget. Further, the results indicated that about 36 per cent of the rational households made wrong decisions in buying the crop insurance, and households with fewer family members and a lower portion of non-farming income are more likely to make wrong decisions. Additional education may help these farmers to make better decisions and increase future welfare gain to a potential level of about CNY 275 per hectare on average.- Reproduced s
Keywords: Crop insurance, Welfare, Decision-making, Maze, Agriculture